In situ exsolved FeNi3 nanoparticles on nickel doped Sr2Fe1.5Mo0.5O6−δ perovskite for efficient electrochemical CO2 reduction reaction. Issue 19 (25th April 2019) - Lv, Houfu; Lin, Le; Zhang, Xiaomin; Gao, Dunfeng; Song, Yuefeng; Zhou, Yingjie; Liu, Qingxue; Wang, Guoxiong; Bao, Xinhe
Abstract : In situ exsolved FeNi3 nanoparticles on nickel doped Sr2 Fe1.5 Mo0.5 O6− δ perovskite greatly enhance the performance of the electrochemical CO2 reduction reaction. Abstract : Solid oxide electrolysis cells (SOECs) have attracted increasing attention as a promising device for the electrochemical CO2 reduction reaction (CO2 RR) due to their high efficiency and fast kinetics. Exploring active cathode catalysts for the CO2 RR is highly desirable for the research and development of SOECs. Herein, in situ exsolved FeNi3 nanoparticles on a Sr2 Fe1.35 Mo0.45 Ni0.2 O6− δ (SFMN) double perovskite substrate (FeNi3 @SFMN) is developed to efficiently catalyze the CO2 RR in SOECs. The SOEC with the FeNi3 @SFMN–GDC (Gd0.2 Ce0.8 O1.9 ) cathode shows a current density of 0.934 A cm −2 at 1.6 V and 800 °C, as well as high stability and no coke deposition for 40 h at 1.2 V. CO2 -temperature programmed desorption and quasi in situ Fourier-transform infrared spectroscopy measurements verify the intensive adsorption of CO2 on the FeNi3 @SFMN–GDC cathode. Distribution of relaxation time analysis combined with density functional theory calculations discloses the stimulative activation of CO2 at the interface between the exsolved FeNi3 nanoparticles and the SFMN substrate with abundant oxygen vacancies, which improves the CO2 RR performance at the FeNi3 @SFMN–GDC cathode.